Xenophobia in Niq Mhlongo’s Dog Eat Dog and Kopano Matlwa’s Period Pain - Zewdu, Aklilu Dessalegn; Daniel, Abiye (Jurnal Lingua Idea, 2023)
Xenophobia has been thematized in South African literature by post-apartheid novelists, and they addressed it in different manners. Two post-apartheid authors who dealt with the issue of xenophobia are Niq Mhlongo and Kopano Matlwa in their novels Dog Eat Dog and Period Pain, respectively. This paper aims to examine how Mhlongo and Matlwa portray xenophobia in their novels and explore the ways they employ to neutralize xenophobia. The paper also discusses the causes of xenophobia pointed out in the novels. Therefore, a critical analysis of the novels has been made by the writer using detailed reading and textual evidence. The analysis indicates that South Africans view black foreigners as job stealers, criminals, drug dealers, witches, and bringers of disease. The writers infused the view of black foreign characters on xenophobia to debunk the negative stereotype and attempted to neutralize it by featuring non-xenophobic protagonists. The article also concludes that Mhlongo and Matlwa reveal the role of the media and the scapegoating hypothesis as the causes of xenophobia.